China’s Financial Statecraft under Xi Jinping administration in selected Southeast Asian countries - Jun, Li; Chin, Kok Fay (Penerbit Universiti Kebangsaan Malaysia, 2024)
With China’s economic rise and influence, financial statecraft has increasingly been deployed to serve the country’s national interest. The growth of China’s financial statecraft in the region has drawn greater media and academic attention. Notwithstanding the abundant literature on China’s financial statecraft in Southeast Asia, the previous studies lack a detailed analysis of various financial statecraft instruments deployed by China. To get a better understanding of China’s deployment of financial statecraft over the years under Xi Jinping’s administration, this article fills the gap in the existing literature by delving into various factors that influenced various financial statecraft instruments with respect to the objectives, trends or patterns and agencies involved in the region. Given Xi’s successful bid for continued political rule by eliminating a term limit on the presidency as well as the escalating China-US strategic rivalry, it is important to examine how the interaction of domestic and international forces has shaped the evolution of financial statecraft in Southeast Asia. Due to the changes in domestic politics and shifts in the geopolitics and geoeconomics, an important question that deserves our attention is how these changes has influenced China’s deployment of various financial statecraft instruments in different Southeast Asian countries. The paper focuses on two middle-income countries (i.e., Malaysia and Thailand) and two low-income countries (i.e. Cambodia and Laos) in the region.